Contextual Richness and Word Learning: Context Enhances Comprehension but Retrieval Enhances Retention. Issue 2 (15th March 2018) - van den Broek, Gesa S. E.; Takashima, Atsuko; Segers, Eliane; Verhoeven, Ludo
Abstract: Learning new vocabulary from context typically requires multiple encounters during which word meaning can be retrieved from memory or inferred from context. We compared the effect of memory retrieval and context inferences on short‐ and long‐term retention in three experiments. Participants studied novel words and then practiced the words either in an uninformative context that required the retrieval of word meaning from memory ("I need the funguo ") or in an informative context from which word meaning could be inferred ("I want to unlock the door: I need the funguo "). The informative context facilitated word comprehension during practice. However, later recall of word form and meaning and word recognition in a new context were better after successful retrieval practice and retrieval practice with feedback than after context‐inference practice. These findings suggest benefits of retrieval during contextualized vocabulary learning whereby the uninformative context enhanced word retention by triggering memory retrieval. Open Practices: This article has been awarded Open Materials and Open Data badges. Stimuli and datasets are publicly accessible via the Open Science Framework athttps://osf.io/eujyn . Learn more about the Open Practices badges from the Center for Open Science:https://osf.io/tvyxz/wiki .